Math Anxiety in Elementary School Students: A Scoping Review - Sindi Regina Prisilia; Andhin Dyas Fitriani; Wahyu Sopandi (Universitas Mercu Buana Yogyakarta, 2026)
Math anxiety is a psychological factor that can influence the mathematics learning process and outcomes of elementary school students. Various studies have examined the causes, impacts, and strategies for managing math anxiety, but these findings are scattered across various focus areas. This study aims to map the development of research on math anxiety in elementary school students during the 2021–2025 period. The study used a scoping review method with the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) approach. Articles were searched through the Scopus database using keywords related to math anxiety and elementary school students. The initial search yielded 650 articles. After going through the identification, screening, eligibility, and inclusion stages, 10 articles met the inclusion criteria for analysis. The study results indicate that math anxiety has a negative relationship with mathematics learning achievement, particularly in numeracy, accuracy, calculation speed, and problem-solving. Furthermore, math anxiety is influenced by various cognitive and affective factors, such as working memory, mathematical reasoning ability, learning motivation, self-perception of ability, learning environment, and gender. Several studies also show that female students tend to have higher levels of math anxiety than male students. Other findings suggest that problem-solving and mathematical reasoning skills play a significant role in mitigating the negative impacts of math anxiety. This study concludes that math anxiety is a multidimensional phenomenon that requires attention in elementary school mathematics learning through strengthening mathematical abilities, increasing self-confidence, and creating an emotionally supportive learning environment.